Nghiên cứu đặc điểm chuyển dịch vỏ Trái Đất theo thời gian, lân cận chấn tâm động đất Sumatra 26-12-2004 từ số liệu IGS - Hải, Vy Quốc (Vietnam Journal of Earth Sciences, 2009)
Studies of time-dependent feature of crustal movements caused by the Sumatra Earthquake on December 26, 2004 from IGS data ...